Snapdragons: tortoise! tortoise! - Langford, Jane; Peters, Andy (Oxford University Press UK, 2004)
Tortoise waks up and asks the animals if he should come out of his shell - but the weather isn't good enough. Finally it's a hot sunny day in summer, but tortoise is asleep - so the other animals call Tortise to wake him up